Whey protein fraction based on Q-sepharose anion exchange chromatography - Zianor Azrina, Z. A. (2010)
Whey proteinsarewell known for their nutritional value and had versatile functional properties.The mains proteins present in whey are α-lactalbumin, β-lactoglobulin, immunoglobulin andbovin eserum albumin. In this study, whey protein component is separate into several fractions using Q-Sepharose anion exchange chromatography column. The chromatographic process was run at different pH range from pH5 to pH8. The best separation was achieved at pH6 in which the major protein component can be separated into their individual protein fraction especially contains α- lactalbumin and β-lactoglobulin. The yield of α-lactalbumin and β-lactoglobulin recovered from 2 ml whey at pH 6 was 46% and 98.4% respectively. Fractionation of single and pure protein component from whey can add the value of the wheybased product and these proteins can be used for specific application.